HUBUNGAN PENDIDIKAN DENGAN PEMERIKSAAN INSPEKSI VISUAL ASETAT PADA WANITA USIA SUBUR - Rahmawati, Mega (Jurnal Kesehatan, 2023)
IVA is one of the early detection of cervical cancer by using acetate acid 3-5% by inspect andseen with direct eye observation. This examination is painless, easy, cheap and the results areimmediate. The purpose of this study is to determine the education related to the behavior of women ofchildbearing on IVA examination in the Sukaraja Nuban Public Health Center working area in 2023.The research will be conducted based on quantitative research. The population are all women ofchildbearing age in working area Sukaaraja Nuban Public Heath Center East Lampung with populationare 4950 women. The sample of the research is 370 people or respondent. Statistical test in this studyusing Chi Square test with 95% CI and P value less than 0,05 were considered statistically significant.The result of this research are 96,2% responden that did not check and 55,1% respondents have lowerlevel of education. Based on the result of chi square statistic test known that P value is 0,004, less than0,05 (P value <0,05), there is correlation of education level with behavior of IVA examination on womenof childbearing age in Sukaraja Nuban Public Health Center working area East Lampung in 2023 withOR = 7,870 (1,736-35,682). So, It is suggested to health workers at the Sukaraja Nuban Heath Centerto continuously increase outreach to the community to increase public knowledge about IVAexamination to encourage people’s behavior to want to carry out IVA examination.